2022
DOI: 10.1002/ps.6896
|View full text |Cite
|
Sign up to set email alerts
|

Adipokinetic hormone signaling regulates cytochrome P450‐mediated chlorantraniliprole sensitivity in Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: BACKGROUND: Fall armyworm (FAW, Spodoptera frugiperda) is one of the most destructive and invasive pests worldwide and causes significant economic losses. Intensive and frequent use of insecticides has led to the development of resistance in FAW. Adipokinetic hormone (AKH) have been proven to be involved in insecticide resistance in insects. However, the molecular mechanism underlying chlorantraniliprole resistance mediated by AKH signaling in FAW remains unclear.RESULTS: The expression of SpfAKHR was highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Synergism experiments with inhibitors (PBO/DEM/TPP) further determined the enhanced effects of P450, GST, and CarE on chlorantraniliprole toxicity (Table ). These results suggest that the Ch-R strain we obtained may be mainly caused by enhanced detoxification metabolism to insecticides, which is consistent with the results of previous studies. , At the transcriptional level, many P450 family genes, such as CYP321A8 , CYP321A9 , CYP321B1 , and CYP6AB12 , were upregulated after chlorantraniliprole stress. , In our study, after association analysis of candidate loci and DEGs, the identified genes related to detoxification metabolism were mainly three GST genes (Table ). As a family of multifunctional enzymes, GSTs confer insecticide adaptation through direct metabolism or sequestration of insecticides .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Synergism experiments with inhibitors (PBO/DEM/TPP) further determined the enhanced effects of P450, GST, and CarE on chlorantraniliprole toxicity (Table ). These results suggest that the Ch-R strain we obtained may be mainly caused by enhanced detoxification metabolism to insecticides, which is consistent with the results of previous studies. , At the transcriptional level, many P450 family genes, such as CYP321A8 , CYP321A9 , CYP321B1 , and CYP6AB12 , were upregulated after chlorantraniliprole stress. , In our study, after association analysis of candidate loci and DEGs, the identified genes related to detoxification metabolism were mainly three GST genes (Table ). As a family of multifunctional enzymes, GSTs confer insecticide adaptation through direct metabolism or sequestration of insecticides .…”
Section: Discussionsupporting
confidence: 92%
“…frugiperda has developed resistance to some Bt maize varieties, which increases the dependence on chemical insecticides in almost all areas affected. , Chlorantraniliprole is an anthranilic diamide insecticide that acts on the ryanodine receptor (RyR) and is becoming the main agent for control S. frugiperda in many commercial crops globally currently because of its broad spectrum, high efficacy, and low cross-resistance to conventional insecticides. Field control experiments showed that chlorantraniliprole had a rapid and persistent effect against S. frugiperda, and it was recommended as a first-choice agent to control S. frugiperda by the Chinese Ministry of Agriculture and Rural Affairs in 2020. , However, the unscientific use of chlorantraniliprole has raised concerns about the development of resistance to this compound in S.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations